Intranasal hydrogel of armodafinil hydroxypropyl-β-cyclodextrin inclusion complex for the treatment of post-traumatic stress disorder - Ge Ou; Qian Li; Lin Zhu; Yuanyuan Zhang; Yijing Liu; Xin Li; Lina Du; Yiguang Jin (Saudi Pharmaceutical Journal)
Armodafinil inclusion complex (AIC) hydrogel was prepared and evaluated for its therapeutic effect on Post-traumatic Stress Disorder (PTSD). After computer simulation and physicochemical property investigation, the AIC was formed by lyophilization of armodafinil with ethanol as solvent and hydroxypropyl-beta-cyclodextrin (HP-β-CD) aqueous solution, in which the molar ratio of armodafinil and HP-β-CD was 1–1. The AIC encapsulation efficiency (EE) was (90.98 ± 3.72)% and loading efficiency (LE) was (13.95 ± 0.47)% and it increased the solubility of armodafinil in aqueous solution to 21 times. AIC hydrogel was prepared by adding AIC to methylcellulose (MC) hydrogels (3.33% w/v), and its higher drug release amount and slower release rate were testified by the in-vitro release assay and the rheological test. The mucosa irritation of AIC hydrogel was also evaluated. Healthy group, Model group, Sertraline group with 30 mg/kg sertraline gavage, AIC Hydrogel group with 20 mg/kg AIC hydrogel intranasal administration and AIC Aqueous Solution group with 20 mg/kg AIC aqueous solution gavage were set up for the treatment of mice with PTSD generated from foot shock method. Based on freezing response test in fear-conditioning box and open field test, compared with other groups, PTSD mice in AIC Hydrogel group showed significant improvement in behavioral parameters after 11 days of continuous drug administration and 5 days of drug withdrawal. After sacrifice, the plasma CORT level of PTSD mice in AIC Hydrogel group was elevated compared to Model group. Besides, the western blot (WB) of hippocampal brain-derived neurotrophic factor (BDNF) and amygdala dopamine transporter (DAT) immunohistochemistry sections indicated that AIC hydrogel had a protective effect on the brain tissue of PTSD mice. The brain targeting of intranasal administration was evaluated by fluorescence imaging characteristics of Cy7 hydrogel in the nasal route of drug administration, pharmacokinetics and in-vivo distribution of armodafinil. In short, AIC hydrogel is a promising formulation for the treatment of PTSD based on its high brain delivery and anti-PTSD effect.